(untitled) (Research, Society and Development, 2022)
Introduction: SARS-CoV-2 is a betacoronavirus belonging to the Nidovirales order of the Coronaviridae family. It is a virus that became evolutionarily able to interact with transmembrane enzymes (ACE 2) occuring in human body’s cells and, therefore, replicating inside them. SARS-CoV-2 might produce a cytokyne storm on human’s organism, causing several systemic damages to the patients. Objective: Describe the main aspects about viral characterization, physiopathology, systemic consequences, as well as the infection’s diagnosis. Methodology: It is about a literature review concerning academical articles available on the following database: PubMed, SciElo, UPTODATE and LILACS, using the following descriptors: COVID-19, SARS-CoV-2 and COVID-19 pandemic. Discussion: SARS-CoV-2’s cell’s entrance may generate multiple inflammatory processes on human’s organism. Since there is ACE 2 receptors on many organs cells, the virus is able to produce systemic injuries. Lung lesions can be identified on the main imaging tests there is, thus helping to comprehend the prognosis and treatment of the patients. Due to the virus agression against the organism, many patients complain about some symptoms that remain even after infection’s resolution. Final notes: Throughout this study, it was possible to understand historical aspects over coronavirus, its variants, the SARS-CoV-2-induced cytokyne storm, as well as systemic repercussions during and after the infection and the available diagnostic methods too.